Rheumatoid Arthritis Associated with the Use of Sandostatin® LAR® Depot in a Patient with Pancreatic Neuroendocrine Tumor. An Association or a Coincidence? The First Case Report - Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2011)
Context Sandostatin® LAR® depot is a synthetic analogue of the naturally occurring hormone somatostatin and is indicated for certain patients with acromegaly and severe diarrhea and flushing episodes associated with metastatic carcinoid tumors and for the long-term treatment of the profuse watery diarrhea associated with VIP-secreting tumors in patients in whom initial treatment with immediate release Sandostatin® injection has been shown to be effective and tolerated. The most common toxicities include biliary disorders, gastrointestinal disorders, injection-site pain, hypoglycemia and hyperglycemia. Rheumatoid arthritis or similar toxicities have not been associated with Sandostatin® LAR® depot. Case report We present a 53-year-old female with a history of neuroendocrine tumor of the pancreas with metastasis to the liver, lung developed joint pains in the hands as well as feet accompanied with intermittent swelling in the morning and pain in the bilateral joints in the hands as well as feet following 45th cycle of Sandostatin® LAR® depot at a dose of 30 mg. All the work-up including rheumatoid factor, anti nuclear antibody, cryoglobulins were within normal limits except her erythrocyte sedimentation rate was elevated. No radiological abnormalities were revealed. Her symptoms improved after we reduced the dose to 20 mg. Discussion Her Naranjo scale was 7, suggesting a probable relation. The patient had four signs and symptoms as required by the American College of Rheumatology for the diagnosis of rheumatoid arthritis. The association of the rheumatoid arthritis with Sandostatin® LAR® depot may be a rare complication but with the extended use beyond acromegaly and carcinoid to acute esophageal variceal bleeding, pancreatic pseudocysts, gastrointestinal, and pancreatic external fistulae, short bowel syndrome, a dumping syndrome and acquired immunodeficiency syndrome-related refractory hypersecretory diarrhea, physicians should be made aware of this probable toxicity. Further research is warranted to understand this association. Image: NY-Presbyterian Hosp from water jeh (by Jim Henderson). Wikimedia Commons.